How Salmonella oxidises H 2 under aerobic conditions - Parkin, A; Bowman, L; Roessler, M; Davies, R; Palmer, T; Armstrong, F; Sargent, F (2012)
Salmonella enterica serovar Typhimurium is a Gram negative bacterial pathogen and a common cause of food-borne illness. Molecular hydrogen has been shown to be a key respiratory electron donor during infection and H 2 oxidation can be catalysed by three genetically-distinct [NiFe] hydrogenases. Of these, hydrogenases-1 (Hyd-1) and Hyd-2 have well-characterised homologues in Escherichia coli. The third, designated Hyd-5 here, is peculiar to Salmonella and is expressed under aerobic conditions. In this work, Salmonella was genetically modified to enable the isolation and characterisation of Hyd-5. Electrochemical analysis established that Hyd-5 is a H 2-oxidising enzyme that functions in very low levels of H 2 and sustains this activity in high levels of O 2. In addition, electron paramagnetic resonance spectroscopy of the Hyd-5 isoenzyme reveals a complex paramagnetic FeS signal at high potentials which is comparable to that observed for other O 2-tolerant respiratory [NiFe] hydrogenases. Taken altogether, Hyd-5 can be classified as an O 2-tolerant hydrogenase that confers upon Salmonella the ability to use H 2 as an electron donor in aerobic respiration. © 2011 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.